The Characteristics and Complexity of the Nigerian Security Challenges: The Need for a New Strategy - Etebom John Monday (CV The Journal Publishing, 2022)
Nigeria, the world sixth most populous nation, is faced with an array of security challenges like most developing nations in West Africa, North Africa and the Middle East. The level of insecurity in Nigeria has risen to an unprecedented level. No part of the six geopolitical zones or regions could be said to be safe. The security challenges in each region of the country are slightly integrated and peculiar as well. From insurgency, terrorism, banditry to cattle rustling in the North to farmer-herder conflict, kidnapping, bank robbery, secessionist and separatist agitations in the South of the country. No part of the country is free of insecurity. The study investigated the characteristics of the security challenges confronting the country and analyzed its peculiarities in the six geopolitical zones. The study revealed that the security challenges ravaging the country were domestically created and interrelated. Inversely, it would require some domestic dynamic military cum pragmatic socio-political approaches to quell. The study adopted a quantitative method of analysis and drew from the benefit of insight and experience of the author who had served in the Nigerian military. It further recommended new inclusive security and political strategies for quelling the uprising in the country.